Design and Validation of Augmented Reality-Based Student Worksheets for Polyhedra Material in Improving Students’ Spatial Abilities: - Sri Winarni; Ade Sri Wulandari Siregar; Marlina Marlina; Rohati Rohati; Ade Kumalasari (Indonesian Journal of Mathematics Education, 2023)
This study aims to develop and test the quality of augmented reality-based student worksheets (LKPD) that can improve students' spatial abilities. This type of research is development research using the Plomp development model, which consists of the initial investigation stage, design, realization, tests, evaluations, revisions, and implementation. The data collection techniques used in this study were observation, interviews, questionnaires, and tests. The instruments used were expert validation sheets, observation sheets, interview guidelines, teacher and student response questionnaires, learning outcomes tests, pre-test questions, and student spatial ability post-test questions. The validation results by design experts and Student Worksheet material experts were 89.09% and 92%, respectively, in the very valid category. In addition, the practicality of Student Worksheets seen from the teacher response questionnaire of 80.00% was classified as practical, and the score of the student response questionnaire in small group trials with 9 students was 81.11% in the very practical category. The effectiveness was shown by 77% of students completing the learning outcomes test, 19 students experiencing moderate spatial ability improvement, and 3 students experiencing high spatial ability improvement, with a percentage of N-Gain effectiveness obtained 61.8% with moderately effective criteria. Based on the results of the study, it can be concluded that augmented reality-based Student Worksheets for polyhedra materials that have been developed are suitable for use as learning teaching materials to improve students' spatial abilities.